Analisa prakmatik pelanggaran maksim percakapan dalam iklan mie sedaap: sebagai proses kreatif pembuatan iklan - Dhyaan Annisa Djuita Nugroho (Fakultas Ilmu Komunikasi Universitas dr. Soetomo, 2020)
This study concerns with flouting the conversational maxim as a creative process in making advertisement. The objective of this study is to know how the conversational maxim are flouted to produce a creative advertisements. The writer formulates the following statements: (1) What kinds of conversational maxims are flouted in the source of data? (2) How do the copywriters flout the maxims? (3) What creative process come out as the result? The writer applies the pragmatics theory to find the addresser and addressee, the context of the utterances, the goals of the utterances, and the act of the utterances. She applies the theory of conversational maxim proposed by H. P. Grice, the theory of communication and advertisements. From the study, she finds out that the copywriters flout the maxim of quality by giving wrong or illogical statement; the maxim of manner by giving ambiguous statement; the maxim of relevance by giving irrelevant response; and maxim of quantity by giving too much information. There are 12 kinds of creative process namely: to attract consumers, to create humorous effect, to incite imagination and curiosity, building image, to persuade people, to influence emotion, building the setting, delivering moral, efficiency in language use and the co-text support the message.